Gallstone ileus-induced intestinal obstruction in a 38-year-old patient with a history of three pregnancies and cesarean section: a case report - Villegas-Coronado, Lucía (2024)
Gallstone ileus-induced intestinal obstruction is a rare but significant condition that occurs when a gallstone becomes lodged in the gastrointestinal tract. Major risk factors for gallstone ileus-induced intestinal obstruction include older age, female sex, diabetes, history of gallbladder disease such as gallstones, as well as previous gallbladder-related surgical procedures such as cholecystectomy. Pregnancy is also a known risk factor for gallstone disease. We present the case of a 38-year-old patient with a history of three cesarean sections and no apparent comorbidities. Prior to her visit to the emergency department, the patient experienced moderate colicky abdominal pain in the lower abdomen for two days. The physical examination revealed diffuse abdominal tenderness, predominantly in the right iliac fossa, along with signs of irritation of the peritoneum. Laboratory tests showed a leukocyte count of 11,490 cells/µl and neutrophilia of 85.6 %. Following an exploratory laparotomy, the suspected diagnosis of gallstone ileus was confirmed. An enterolithotomy was performed, and the patient experienced good post-surgical progress. In conclusion, it is important to consider gallstone ileus-induced intestinal obstruction among patients with relevant symptoms and medical history. This case report highlights the importance of considering gallstone ileus-induced intestinal obstruction among patients with gastrointestinal symptoms and a history of pregnancy. Early diagnosis and intervention are crucial to prevent serious complications.